China’s shifting position in the global climate change - Elmalı, Burak. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Over the past two decades, China has emerged as a rising economic power with excessive amounts of carbon emissions that directly contribute to global climate change. Being a part of the international regime for global climate change regime, the country has also pursued a different set of policies to address the issue both domestically and internationally. This is also apparent in China’s vast investment landscape. The country has shown shifting patterns from a fossil-oriented investor to a more climate-friendly one. Also, it has proactively engaged in the regime's institutional platforms and revealed strong signals to cooperate on this global issue. This thesis aims to answer why China decided to move in such a direction and showed shifts in its investment allocation preferences by contextualizing foreign investments between 2005 and 2022. In contrast to the arguments based on liberal institutionalism and regime theory, China’s moves can be better attributed to realist considerations and strategic calculations within the scope of its incentive structure. This consists of economic gains and reputational benefits, both of which led China to increase its relative gains and reduce international pressures. From energy and transport investments to positioning in international negotiations, several cases are presented to demonstrate how China operationalizes its incentive structure. Combining climate change with some prominent international relations theories, this thesis contributes to an interest- based understanding of China’s climate policies and places them into a broader context of an incentive structure framework.
Keywords: Climatic changes -- China.; China -- Environmental conditions.